2018
DOI: 10.1111/imcb.12000
|View full text |Cite
|
Sign up to set email alerts
|

The anti‐inflammatory IFITM genes ameliorate colitis and partially protect from tumorigenesis by changing immunity and microbiota

Abstract: Inflammation plays pivotal roles in different stages of tumor development. Screening for predisposing genetic abnormalities and understanding the roles these genes play in the crosstalk between immune and cancer cells will provide new targets for cancer therapy and prevention. The interferon inducible transmembrane (IFITM) genes are involved in pathogenesis of the gastrointestinal tract. We aimed at delineating the role of IFITM3 in colonic epithelial homeostasis, inflammation and colitis-associated tumorigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 49 publications
1
47
0
1
Order By: Relevance
“…82 IFITM3 deficiency led to exacerbation of chemical-induced colitis, with increased infiltration of macrophages and effector T cells to the colon lamina propria, and biased CD4 + Th differentiation to Th17. 82 That this exacerbated colitis was attributable to cells of the haematopoietic system was confirmed in bone marrow transplantation experiments. Interestingly, IfitmDel À/À mice developed spontaneous chronic colitis, indicating that other IFITM proteins are also protective against colitis, and both Ifitm3 À/À and IfitmDel À/À showed changes in the faecal microbiota.…”
Section: The Ifitm Family In Allergic and Inflammatory Diseasementioning
confidence: 87%
See 1 more Smart Citation
“…82 IFITM3 deficiency led to exacerbation of chemical-induced colitis, with increased infiltration of macrophages and effector T cells to the colon lamina propria, and biased CD4 + Th differentiation to Th17. 82 That this exacerbated colitis was attributable to cells of the haematopoietic system was confirmed in bone marrow transplantation experiments. Interestingly, IfitmDel À/À mice developed spontaneous chronic colitis, indicating that other IFITM proteins are also protective against colitis, and both Ifitm3 À/À and IfitmDel À/À showed changes in the faecal microbiota.…”
Section: The Ifitm Family In Allergic and Inflammatory Diseasementioning
confidence: 87%
“…Interestingly, IfitmDel À/À mice developed spontaneous chronic colitis, indicating that other IFITM proteins are also protective against colitis, and both Ifitm3 À/À and IfitmDel À/À showed changes in the faecal microbiota. 82…”
Section: The Ifitm Family In Allergic and Inflammatory Diseasementioning
confidence: 99%
“…AF12 sp. is an under-characterized microbe, with some literature nding a correlation between higher abundance and lower body weight, although some evidence is con icting [100][101][102][103]. Additionally, AF12 sp.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the exact topology of IFITMs is still to be investigated. IFITM proteins are involved in the regulation of many activities, such as tumorigenesis [4] and immune signal transduction [5]. Most importantly, it has been reported that IFITM proteins have a broad antiviral spectrum in recent decades.…”
Section: Introductionmentioning
confidence: 99%